P PENJARINGAN BAKAT SISWA-SISWI SMP/MTS PADA CABANG OLAHRAGA ATLETIK MELALUI MADRASAH ISLAMIC COMPETITION (MIC) 2024 - Ulum, Shohibul; Yogo Dwi P, Ajodyo; Sulaiman, Ahmad; Sumanjaya, Wahman (ABIDUMASY, 2024)
The lack of athletic competitions in Jember Regency, causing a decrease in achievement. Therefore, Madrasah Islamic Competition (MIC) cooperates with PASI (Indonesian Athletics Association) Jember Regency to organise competitions, one of which is athletic sports, especially running numbers. Madrasah Islamic Competition (MIC) is a competition event held by MAN 2 Jember to facilitate the talents and potential of junior high school / middle school students throughout Besuki Prefecture. One of the branches contested is the 100 m and 400 m run. Talent screening in this athletic sport is the main focus, with the aim of identifying and developing the potential of young athletes who can represent their schools and regions in larger competitions. This service activity aims to make it easier for PASI (All Indonesian Athletics Association) Jember Regency to choose athletes who are eligible to compete in the PORPROV (Provincial Sports Week). This service method uses several stages including; (1) Preparation Stage, (2) Implementation Stage, (3) Evaluation and Reporting Stage. This service activity aims to facilitate the coaches and administrators of PASI (All Indonesian Athletics Association) Jember Regency in selecting athletic athletes to be prepared for the PORPROV (Provincial Sports Week) event. So that students have the motivation to be selected to join the Jember Regency contingent in facing the event.